ANALISIS FAKTOR RISIKO ASUPAN ZAT GIZI DENGAN KEJADIAN OBESITAS SENTRAL PADA WANITA DEWASA DI KECAMATAN NANGGALO KOTA PADANG TAHUN 2017 - Zulferi Tessa Asriati (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
ABSTRACT This study aims to determine the risk factors of nutrient intake to the incidence of centralobesity in adult women in Nanggalo District of Padang City 2017.The research was conductedfrom August 2016 until June 2017 in district of Padang City. The design of this research iscase control study. Pupulation of this research were all adult women in district of Padang City,with 18 case samples and 18 controls. The sampling technique is purposive sampling. Datacollection was done by anthropometric measurement and interview using SQ-FFQ format. Thestatistical test used for data processing is chi square and odds ratio with 95% confidence level.The results showed that risk factor of nutrient intake was related to the occurrence of centralobesity in adult women in Nanggalo District is carbohydrate intake (p=0,000 OR=20,8),protein intake (p=0,002 OR=10), fat intake (p=0,000 OR=20,8), vitamin A intake (p=0.044OR=4.09) and vitamin C intake (p=0.001 OR=12.3). While calcium intake (p=0,301 OR=3,4)was not a risk factor of central obesity and intake of zinc (p=0,005 OR=0,1) was protectivefactor of central obesity. The high incidence of central obesity in adult women in NanggaloDistrict of Padang City, is expected in the community, especially adult women to pay attentionto eating patterns both intake of macro and micro nutrients to prevent further complicationssuch as degenerative diseases.Keywords : Central Obesity, Intake of Nutrition